An Approach for Displaying the Relations among Main Elements of Object-Oriented Programs - Kayvan Kaseb; Mohammad Sayedi (International Journal of Electrical and Computer Engineering (IJECE), 2013)
An appropriate understanding of the source code is one of the necessary steps for resolving errors and improving code and design. Two fundamental aspects in Object-Oriented Programs are program elements including classes and packages, and the relations among them. In this paper, a multi-step approach has been presented and implemented for recovering and displaying main elements of an Object-Oriented Program including classes, packages, and the relations among them. This approach has been done through three steps; first, the set of classes, packages, and the relations among them are obtained automatically from the program source code. Second, a code is injected to the program source code to register the information needed during runtime. Finally, the information obtained from previous steps is displayed. The results of this approach can be used for automatic documentation, teaching programming, better understanding and evaluating Object-Oriented Programs, reverse engineering methods for detecting program strengths and weaknesses.DOI:http://dx.doi.org/10.11591/ijece.v3i5.4031